Deep learning based channel estimation for OFDM system - Ahmad Erfan Hilme Haji Bakri (Nanyang Technological University, 2023)
Channel estimation is a critical component in wireless communication systems, including orthogonal frequency division multiplexing (OFDM) systems. Traditional methods for channel estimation often have limitations in terms of accuracy and performance, particularly in complex wireless environments. Throughout many different applications, deep learning (DL) has proven itself to be a reliable tool to be integrated in our technologies.